Inovasi Ice Breaking Berbasis Outbound untuk Guru Pendidikan Anak Usia Dini - Riswandi, Fitta Nurisma (Universitas Nusantara PGRI Kediri, 2023)
The outbound-based icebreaking innovation was motivated by boredom carried out by PAUD/TK/RA teachers because educating children of developmental age requires a lot of emotional patience in a closed classroom, so if it is done outside the outbound-based classroom, emotional relaxation will be felt. , making the participant's condition relaxed and comfortable. This research aims to create a book product about outbound-based icebreaking innovations for PAUD teachers, such as: guessing the name of the prophet, guessing short letters in the Koran, and guessing prayers in everyday life but done outside the classroom. The method for using ADDIE development includes analysis, design, development, implementation, and evaluation. The research results show that the validator of one attraction received a score of 80 in the good category, effectiveness received a score of 75 in the good category, and practicality obtained a score of 80 in the good category. The second validator of attractiveness got a score of 85 in the good category, effectiveness got a score of 80 in the good category, and practicality got a score of 80 in the good category. Validators of three material understanding abilities obtained a score of 85 in the good category. Conclusion Outbound-based icebreaking innovation is suitable for use by PAUD/TK/RA teacher participants.